رسول اللهﷺ كى زندگى ميں فرح وحزن كے واقعات اور ان كے اثرات - Zainb Rehman; Dr. Ali Tariq (Seerat Studies, 2024)
The study of Seerah has always held a distinguished place among Islamic sciences, as it is rooted in the life of the Prophet Muhammad (PBUH), which serves as a beacon house and guiding tower for all dimensions and aspects of human existence. Life, in its essence, is never free from moments of joy and sorrow, as these emotions are intrinsic to human nature. Given this reality, individuals require continuous guidance on how to navigate and express these emotions appropriately. It is only natural, then, that the life of the Mercy to the Worlds (PBUH) being the noblest example for the believers encompasses profound and practical examples of such emotional expressions. This article presents selected incidents from the blessed life of the Prophet (PBUH), analyzing them to highlight the etiquettes of expressing joy and grief and point out the transformative effects these practices can have on individuals and society.